Analysis of the Development of the Service Sector in the Republic of Uzbekistan - Abdumadjit, Suyunov; Zayniddin, Karjavov; Mamatovna, Suyunova Yaxshigul (European Journal of Life Safety and Stability (2660-9630), 2022)
The main structural sectors of the economy of Uzbekistan are industry, construction, agricultural sector, consumer goods market, trade and services. This article provides an analysis of the role of the service sector in the growth of our economy.